Early Cycladic Sculpture in Context from Beyond the Cyclades : From Mainland Greece, the North and East Aegean - Marthari, Marisa (Oxbow Books, Limited, 2019)
Cover -- Book Title -- Copyright -- Dedication -- Contents -- List of contributors -- Abbreviations -- List of figures -- List of tables -- Preface -- 1 Introduction: Colin Renfrew -- Before the Bronze Age -- 2 Past in the past: examples of Neolithic figurines from mainland Greece and Early Cycladic anthropomorphic imagery: Fanis Mavridis -- Attica -- 3 An Early Cycladic figurine from the Acropolis of Athens: Lena Papazoglou-Manioudaki -- Appendix: optical examination of a Cycladic-type marble figurine from the Acropolis and vessels from Makronisos in the National Archaeological Museum, Athens, Dimitris Tambakopoulos &amp -- Yannis Maniatis -- 4 Aghios Kosmas revisited: the Cycladic figurines from the Early Helladic site at Aghios Kosmas in Attica: Katerina Kostanti &amp -- Alexandra Christopoulou -- 5 Two Cycladic figurines from subterranean Chamber III, in the Early Helladic settlement at Koropi, eastern Attica: Olga Kakavogianni -- 6 Cycladic figurines from Tsepi, Marathon: Maria Pantelidou Gofa -- 7 Fragment of an Early Cycladic folded-arm figurine from the acropolis of Brauron: Konstantinos Kalogeropoulos -- 8 An Early Helladic figurine from Loutsa, Attica: Maria Stathi -- 9 A schematic figurine from the area of Kephisos in Aegaleo, Αthens: Eleni Asimakou -- 10A FIGURINE FROM A TOMB ATMANDRA IN WESTERN ATTICAKalliopi Papangeli -- 11 A fragmentary Cycladic figurine from Nea Kephisia, Attica: Theodora Georgousopoulou -- 12 Cycladic-type figurines from the Early Helladic cemetery of Asteria at Glyfada, Attica: Konstantina Kaza-Papageorgiou -- Appendix: the bioarchaeological context of the Asteria figurines, Eleanna Prevedorou -- Peloponnese -- 13 Early Cycladic sculpture from Delpriza in the southern Argolid: Angeliki Kossyva -- 14 Cycladic figurine from the sanctuary of Apollo Maleatas in Epidauria: Vassilis Lambrinoudakis.